EFFECTS OF EXTRACT FROM ASTRAGALUS GLYCYPHYLLOIDES ON ARBONTETRACHLORIDE-INDUCED HEPATOTOXICITY IN WISTAR RATS - RUMYANA SIMEONOVA; ILINA KRASTEVA; MAGDALENA KONDEVA-BURDINA; NIKO BENBASSAT (International Journal of Pharma and Bio Sciences, 2013)
The antioxidant effect of aqueous-ethanolic extract from Astragalus glycyphylloides (Fabaceae), and its protection against carbon tetrachloride-induced hepatotoxicity were investigated in male Wistar rats. For seven consequent days the animals were treated orally with A. glycyphylloides extract (EAG) (100 mg/kg). Two hours after the last administration the animals were charged with carbon tetrachloride (10%, 1,25 mL/kg p.o.). The rats were sacrificed 18 hours later by decapitation. Carbon tetrachloride, administered alone, induced significant hepatotoxicity, manifested with reduced glutathione (GSH) depletion, increased level of malondialdehide (MDA) and reduced antioxidant defense. EAG pretreatment, however, completely reversed the effect of carbon tetrachloride on GSH and MDA concentrations and antioxidant enzyme activities as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione-S-transferase (GST). The results of this study showed an antioxidant activity of extract from Astragalus glycyphylloides and its protective effect against carbon tetrachloride-induced oxidative stress and hepatotoxicity.